Antifungal Efficacy and Physical Properties of Poly(methylmethacrylate) Denture Base Material Reinforced with SiO2 Nanoparticles. Issue 6 (15th October 2020) - Alzayyat, Sara T.; Almutiri, Ghadah A.; Aljandan, Jawhara K.; Algarzai, Raneem M.; Khan, Soban Q.; Akhtar, Sultan; Matin, Asif; Gad, Mohammed M.
Abstract: Purpose: To evaluate the effect of the addition of low concentration of silicon‐dioxide nanoparticles (nano‐SiO2 ) to poly(methylmethacrylate) (PMMA) denture base material on Candida albicans adhesion, surface roughness, contact angle, hardness, and translucency. Materials and methods: A total of 150 acrylic disks were fabricated from heat‐polymerized acrylic resin and specimens were divided into 3 groups of 50 per test. They were further subdivided into 5 subgroups (n = 10) according to the concentration of nano‐SiO2 : control (no addition) and four tested groups modified with 0.05, 0.25, 0.5, and 1.0 wt% nano‐SiO2 of acrylic powder. Slide count and direct culture methods were used to measure C. albicans count (CFU/mL). The surface roughness values ( R a ; μm) were determined using a profilometer. The contact angle ( o ) measurement was performed by a goniometer using the sessile drop method. Vickers hardness was used to analyze surface hardness. Translucency was measured using a spectrophotometer. Data analysis was conducted through analysis of variance and Tukey's post hoc tests (α = 0.05). Results: Compared to the control group, direct culture and slide count methods illustrated a significant decrease in C. albicans count ( p ˂ 0.001) with the addition of nano‐SiO2, and this decrease was correlated with the concentration of nano‐SiO2 . The addition of nano‐SiO2 significantly decreased the contact angle ( p ˂ 0.001), whereas hardness and surface roughness significantly increased ( p ˂ 0.001). The addition of nano‐SiO2 significantly decreased translucency ( p ˂ 0.001), and this decrease was concentration dependent. Conclusion: Addition of low concentration of nano‐SiO2 decreased C. albicans adhesion to PMMA denture base resin. Also, low additions of nano‐SiO2 have positive effects on contact angle and hardness, whereas surface roughness and translucency were adversely affected at high concentrations.